Study on Shear Behavior of Concrete-polymer Cement Mortar at Elevated Temperature - Khuram Rashid; Tamon Ueda; Dawei Zhang (Civil Engineering Dimension, 2016)
In this experimental and analytical work, interfacial shear strengths were evaluated at material and member level. Bi-surface shear strength was performed at material level and three-point bending test was conducted at member level. Beams were strengthened by adding steel reinforcement at soffit level and covered by spraying polymer cement mortar (PCM). After curing, strengthened RC beams were exposed to 60 ℃ for 24 hours and tested in three point loading test. Flexural capacity, load deflection relationship and failure modes were observed and compared with the strengthened beams tested at 20 ℃. Reduction in flexural capacity was observed with temperature, failure mode was also shifted from flexural mode to debonding mode of failure at elevated temperature. Ultimate shear load and failure modes were predicted by truss analogy approach. Debonding model was proposed by incorporating bi-surface interfacial shear strength, close agreement were observed between experimental and predicted values.